Pengaruh Kejelasan Sasaran Anggaran, Sistem Pelaporan Terhadap Akuntabilitas Pemerintah Dan Komitmen Organisasi sebagai Variabel Moderating - Nurji, Nurji; Asmoni, Thatok; Surasni, Surasni (E-Jurnal Akuntansi, 2019)
The purpose of this study is to determine the effect of clarity of budget targets and reporting systems on village government performance accountability and organizational commitment as a moderating variable on village government. The data analysis method uses multiple linear regression models and residual tests for moderating variables. The results of this study indicate that simultaneous clarity of budget targets and reporting systems significantly influences the performance accountability of village government agencies. Partially, the reporting system has a significant positive effect on the accountability of the performance of village government agencies, while the variable clarity of budget targets does not affect the accountability of the performance of village government agencies in the West Sakra District, East Lombok Regency. Keywords : Budget Target Clarity; Reporting System; Organizational Commitment Performance Accountability Of Government Agencies.